HEPATOPROTECTIVE ROLE OF EXTRACTS OF MOMORDICA CHARANTIA L. IN ACETAMINOPHEN-INDUCED TOXICITY IN RABBITS - K. Zahra; M. A. Malik; M. S. Mughal; M. Arshad; M. I. Sohail (Journal of Animal and Plant Sciences, 2012)
An analysis of different serum enzymes including ALT, AST, ALP and LDH was carried out to evaluate the hepatoprotective and hepatocurative effects of Momordica charantia. The study was divided in two phases. In first the phase, liver toxicity was induced in rabbits with administration of acetaminophen, and then Momordica extract was given and hepatocurative effects were observed. The results indicated significant decrease in the elevated concentrations of these enzymes in acetaminophen-intoxicated rabbits. In the second phase, the extract of Momordica was given to the rabbits orally for 10 and 15 days respectively. Then, the animals were administered with acetaminophen and hepatoprotective effects of Momordica were observed. The hepatoprotective effects of Momordica extract was found to be more effective after 15 days as there was less elevation of the serum enzymes after liver damage.
Keywords: Serum Enzymes; Hepatoprotective; Hepatocurative; Momordica charantia; Acetaminophen